S18 Activation of nociceptin orphanin FQ (N/OFQ) – N/OFQ peptide (NOP) receptor system plays a key immunomodulatory role in asthma. (14th November 2013) - Singh, R; Sullo, N; Matteis, M; Spaziano, G; McDonald, J; Saunders, R; Woodman, L; Urbanek, K; DeAngelis, A; DePalma, R; Berair, R; Pancholi, M; et al.
Abstract : Asthma is a complex heterogeneous disease characterised by variable airflow obstruction, bronchial hyper-responsiveness, airway inflammation and remodelling. The heptadecapeptide nociceptin/orphanin FQ (N/OFQ) is the endogenous ligand for the N/OFQ peptide (NOP) receptor, a non-opioid member of the opioid receptor family. The role of N/OFQ-NOP system in asthma is uncertain. We sought to evaluate N/OFQ-NOP expression in healthy and asthmatic human airway tissues and relate this to an established animal model of asthma. NOP expression in human airway cells was investigated predominantly by qRT-PCR. The functional role of N/OFQ on human airway structural and immune cells was then interrogated using a range of functional assays including proliferation, migration, collagen gel contraction and wound healing. We further investigated the functional role of N/OFQ in vivo using ovalbumin-sensitised mice. NOP expression was detected in human airway smooth muscle cells (HASM; mean?C? = 11 ± 0.7, n = 13), bronchial epithelial cells (HBEC;mean?C? = 10 ± 0.49, n = 12), lung mast cells (mean?C? = 7 ± 0.64, n = 5) and peripheral blood eosinophils (mean?C? = 10.4 ± 1.2, n = 16). N/OFQ inhibited chemoattractant-induced migration of mast cells and eosinophils (see Figure). N/OFQ stimulated significant HBEC wound closure with 49.62 ± 3.58% (p < 0.001, n = 8) of the wound area healed relative to the control (30.88 ± 4.13%, n = 8)18 h post-wound. Similarly N/OFQ significantly promoted HASM wound closure (p < 0.01). Our findings showed that SCF-stimulated IL-8 release (4.43 ± 0.69 fold over control, p < 0.01, n = 7) was significantly inhibited by N/OFQ (3.32 ± 0.56 fold over control, p < 0.01, n = 7). Ex vivo human studies demonstrate significantly (p < 0.01) increased endogenous N/OFQ in asthmatic airways relative (sputum N/OFQ:59.02 ± 2.57 pg/ml, n = 26) to healthy airways (sputum N/OFQ:44.69 ± 0.43, n = 10) and identifies eosinophils as a potential source for these. Pre-treatment with N/OFQ was shown to significantly reduce agonist-induced bronchial hyper-responsiveness using in vitro (p < 0.01) and in vivo models (p < 0.001). Ex vivo animal studies show that N/OFQ significantly inhibits release of inflammatory mediators including IL4, IL5, IL12, IL13 and inflammatory cell recruitment including mast cells and eosinophils within the airways. Further mucus hyper-secretion was also reduced following N/OFQ pre-treatment in these models. This is the first study to perform a comprehensive and complementary in vivo and in vitro study of the expression and actions of the N/OFQ-NOP system in the airways and provide evidence for a role of NOP activation in the management of asthma.